Breeding potential of criollo lechero tropical bulls - Estrella-García, Andrea Guadalupe; López-Ortíz, Silvia; Canseco-Sedano, Rodolfo; Pérez-Hernández, Ponciano; Ahuja-Aguirre, Concepción del Carmen; Guerrero-Hernández, Jonathan (Ecosistemas y Recursos Agropecuarios, 2021)
Criollo Lechero Tropical livestock (CLT) have desirable characteristics for tropical livestock production. However, the reproductive performance of CLT bulls at different ages and in different seasons of the year has not been evaluated under tropical climate conditions. In this study, eight bulls were assigned to two age groups: 1) G1 (n=5): bulls at age 19.3 ± 0.4 months and 260 ± 9 kg of live weight, and 2) G2 (n=3): bulls at age 30.5 ± 3.1 months and 371 ± 29 kg of live weight. Throughout one year, libido was evaluated in a 0 to 10-scoring mehod and serum testosterone concentrations were determined. In the different seasons of the year, libido was scored 8 to 10 in both groups of bulls. Bulls from G2 had higher concentrations of testosterone (P